Selección de segregantes F3 de arroz japónico (Oryza sativa L. ssp. japonica) con características agronómicas superiores para el desarrollo de nuevas variedades - Torres Franco, Cinthia Aracely (2018)
SUMMARY In the present research on the "Selection of segregants F3 of japonica type rice (Oryza sativa L. ssp. japonica) with superior agronomic characteristics for the development of new varieties", was conducted in the El Palmar Experimental Farm belonging to the Technical University of Babahoyo, CEDEGE Project area, province of Los Ríos, located at Km 10.5 of the Babahoyo - Montalvo road. The evaluated variables were; Vigor, Flowering (days), Vegetative cycle (days), Number of tillers per plant, No. of panicles per plant, Length of the flag leaf (cm), Width of the flag leaf (cm), Length of leaf 2 (cm), Width of leaf 2 (cm), Plant Height (cm), Panicle Length (cm), Grain / panicle, Sterility (%), Shelling (%), 1000 Grain Weight (g), Grain Length (mm), Shelled Grain Width (mm) , White Center (%), and Presence of edge (%). The statistical analyzes used were: analysis of variance and the Tukey test 5%, analysis of Principal Components, the analysis of Conglomerates and the analysis of the Relative Variability. The obtained results in the present work, with respect to the variable number of tillers, were observed lines such as JP001 / JP003 P * - # 19, which achieved an average of 44 tillers; however, others were contrasting as the line JP002 / DH P14-6 that reached only 9 tillers per plant. As regards the panicle number per plant, some lines were expressed in a superior way, such as DH / JP002 P1 # 28, JP002 / JP004 P 7-7 and JP001 / JP003 P * - # 19, which presented averages which were in the range of 35 to 43 panicles per plant. Line DH / JP003 P * 3-44, reached an average of 119.63 cm of plant height, unlike JP001 / JP004 P2-14, which obtained an average of 51.25 cm. However, it should be mentioned that heights among 80 to 100 cm in rice, can favor its plant architecture and can be less prone to lodging. Line JP001 / JP003 P175-long grain, achieved the highest value of grains per panicles with an average of 223.85, as an indication of better production. With respect to the yield (g / plant), the line JP003 / JP00 P169-long grain achieved the best value with an average of 100.34 g; however, the analysis of relative variability (%) allowed the selection of eight lines of better behavior, as mentioned below: JP003 / JP00169-P1 long, JP001 / JP003 P3-13, JP002 / JP003 P * -P5, JP001 / JP003 P9 # 15, JP001 / JP003 P3 # 14, JP003 / JP001 P1 # 1, DH / JP004 P6A- # 38 and JP002 / DH P14-6, lines that will be used for subsequent studies. In this study, it is recommended to give continuity to the selected lines and take them to the next generation (F4), for the selection of elite lines. The lines of good behavior, quality evaluations should be made milling and culinary grain, pests and diseases, nutrition and other studies that complement the research to achieve future release of varieties with excellent characteristics. Key words: Rice, genetic variability, japonica subspecies, selection, F3 segregation.